Discovery of a new Lower Cretaceous Wealden-type ostracod fauna from the Bouhedma Formation, Central Tunisian Atlas, North Africa. (November 2021) - Chnayna, Manel; Sames, Benjamin; Trabelsi, Khaled; Houla, Yassine; Hanini, Amine; Elferhi, Faycel; Skanji, Ahmed; Wagreich, Michael; Soussi, Mohamed
Abstract: Micropalaeontological investigations of the Bouhedma Formation in the Jebel Majoura section from the southern Central Tunisian Atlas revealed four successive ostracod associations (in total 16 species of 13 genera) of higher palaeoenvironmental, and thus far limited biostratigraphic and palaeobiogeographic utility due to poor preservation. The most notable of these is a new upper Hauterivian?–Barremian non-marine Wealden-type ostracod assemblage of high diversity from the Lower Member of the Bouhedma Formation, the first one documented from the southern Central Tunisian Atlas, which consists of 9 species: Cypridea cyrtorostralis, Cypridea aff. tenuis, Cypridea aff. insulae, Cypridea sp., Theriosynoecum cf. fittoni, Vecticypris polita, Alicenula ? leguminella, as well as Klieana sp. and Fabanella sp. The subsequent two ostracod assemblages from the Lower Member are characterized by the brackish species Rehacythereis ? sp., Fabanella sp ., Ilyocypris sp., and Schuleridea ? sp. indicating transition to lagoonal environment. The subsequent ostracod assemblage from two levels of the Middle Member of the Bouhedma Formation is exclusively composed of the euryhaline marginal marine Paracypris sp., and the marine species Antepaijenborchella praealta, Protocythere cf. bedoulensis and Metacytheropteron aff. grosdidieri, reflecting a marine incursion event. The biostratigraphic utility, particularly that based on the non-marine fauna, is limited thus far but the results are consistent with an upper Hauterivian?–Barremian age previously assigned to the Bouhedma Formation from the southern Central Tunisian Atlas, facilitating its regional stratigraphic correlation with coeval series from the northern part of this palaeogeographic domain. The discovery of Tunisian Wealden-type non-marine ostracods from the southwestern margin of the Tethys (North Africa) sheds new light on the dispersal patterns and palaeobiogeography of these ostracods, their potential utility as biostratigraphic tool, as well as on the significance of the north Gondwanan continental basins and peri-Tethyan islands of the Central Tunisian Atlas for recording Early Cretaceous non-marine microfaunas and -floras. Graphical abstract: Image 1 Highlights: First report of an Hauerivian?–Barremian Wealden-type ostracod fauna from the southern Central Tunisian Atlas. First documentation and inventory of non-marine to marginal marine ostracod faunas from the Bouhedma Formation (middle Lower Member) at Jebel Majoura, southern Central Tunisian Atlas. The non-marine fauna is highly diverse and has been retrieved from a limestone using acetolysis. Paleoenvironmental analysis of ostracod faunas documents marine incursion within the mid-to upper part of Lower Member of the Bouhedma Formation.